Evaluation of chloride transport in blended cement mortars containing coal mining waste. (30th November 2018) - Caneda-Martínez, Laura; Frías, Moisés; Medina, César; de Rojas, Mª Isabel Sánchez; Rebolledo, Nuria; Sánchez, Javier
Highlights: Mortars prepared with activated coal mining waste show lower compressive strength. Chloride diffusion is reduced in blended mortars containing activated coal waste. Addition of CMW to cement promotes chloride binding in the form of Friedel's salt. Microstructure in CMW blended cements becomes more refined as the CMW content increases. Abstract: In this study, the effect of the addition of a thermally activated coal mining waste (CMW) on the chloride permeability of blended cements in amounts from 10 to 50% was assessed by salt ponding test. The parameters involved in the infiltration of chloride have been evaluated by XRD, TG and MIP techniques, as well as by electric resistivity measurements. A remarkable improvement in chloride diffusion was found as the CMW content increased, which has resulted in a decrease of one order of magnitude in the chloride diffusion coefficients of specimens containing 50% of CMW (2.7·10 −12 m 2 /s) with respect to OPC samples (20·10 −12 m 2 /s). The chemical analyses have shown that immobilization of chloride ions as Friedel's salt takes place as a result of their reaction with the abundant hydrated aluminate phases formed as a consequence of the high alumina content in CMW. Moreover, it has been observed a refinement of the capillary network with the addition of CMW that has been manifested through a decrease in pore size and a subsequent increase in electrical resistivity.